MAKING STUDENT WORKSHEET INTEGRATED SCIENTIFIC LITERACY FOR PHYSICS PRACTICUM KITS ON DYNAMIC FLUID MATERIAL - Allin Wel Ningsi; Hidayati Hidayati; Amali Putra; Renol Afrizon (Department of Physics Universitas Negeri Padang, 2023)
The use of school facilities and infrastructure has not been used optimally. One of them is rarely using practicum KIT because of the teacher's lack of time to develop worksheets. Schools still apply literacy in reading, writing and numeracy and have not implemented scientific literacy. This application can be done with scientific literacy integrated worksheets for the use of physics practical KIT on dynamic fluid material which is considered in the validity test and practicality. The type of research is research and development (R&D) using the Borg & Gall model in Sugiyono's book. The initial data collection instruments used were questionnaires and interviews conducted by teachers and students. The validation test was carried out by 3 experts, namely Physics lecturers Faculty of Mathematics and Natural Sciences, Padang State University and the practicality test was carried out by 2 Physics teachers and 36 students of class XI science 3. The analytical technique used was descriptive analysis technique. The results of this study obtained a product in the form of student worksheets integrated with scientific literacy for the use of physics practicum KIT on dynamic fluid material. based on product data analysis, a validity value of 0.85 was obtained in the very valid category and the practicality values ​​of teachers and students were 87% and 90.25% respectively in the very practical category. Thus it shows that the worksheet is integrated with scientific literacy using the physics practicum KIT on dynamic fluid material that is feasible to use in the physics learning process.